Family conflict and the evolution of sociality in reptiles - While, G; Uller, T; Wapstra, E (2009)
Mating systems and parental care are predicted to coevolve because the former dictates the cost-benefit ratio of the latter by affecting genetic relatedness between adults and offspring. Reptiles show only rudimentary forms of sociality and parental care and, hence, could provide important insights into the early stages of the evolution and maintenance of social systems. The skink genus Egernia exhibits the most complex form of sociality and parental care in lizards, with the formation of stable social groups typically consisting of a monogamous pair and their offspring. Here we show that, within a social group, offspring sired by males other than the social father are restricted to the area of the parental home range that is occupied exclusively by the mother. Thus, males rarely tolerate offspring within their home range that they are not genetically related to. This may increase the cost of multiple mating for females and offspring via increased risk of infanticide, reduced parental tolerance, and increased mother-offspring competition. We outline a verbal model for how this could generate a feedback loop in which selection favors reduced multiple mating by females and increased paternal care, thereby setting the stage for the evolution of complex sociality and genetic monogamy.